The university teacher in the digital age (Revista Innova Educación, 2022)
The research analyzed and reflected on the future of university teaching in a globalized-digital world. The study problem shows that a small percentage of teachers have managed to adapt to technological means, mainly in third world countries. In this sense, the objective of this study is to outline ideas to strengthen the profile of the university teacher through the responsible domain of technology. For this, we propose as a thesis, constant teacher training in digital didactics and pedagogy, which inserts us into a new university scientific era. In conclusion, university pedagogy is forced to changes that favor humanity, so thinking today of university teaching without digital technology seems wrong.
Keywords: digital competence; educational cyberculture; university teacher; digital era; teacher profile